Comparison of position and possession games attending to the positional external load. Does player specific position matters? - Asian-Clemente, J. A.; Requena, B.; Beltran-Garrido, J. V.; Galiano, C. (International Journal of Sports Science & Coaching, 2025)
The aims of our study were to compare the differences in external load between position and possession games according to player specific role, and to examine the external load demands of position games across player positions on different pitch sizes. 25 professional players were monitored using GPS during 18 possession (without positional roles) and position games (with positional roles). All games were played in a 9 vs. 9 + 2 floaters format, with each task occurring in Small (<60 m2 per payer), Medium (60-90 m2 per player), and Large (> 90 m2 per player) sizes. Position games showed lower distance covered (DC) for Central-defenders, Fullbacks and Offensive midfielders, as well as reduced high-speed running among Central-defenders compared to possession games (p < 0.05). In contrast, position games presented larger maximal decelerations for Central-defenders (p < 0.001) and acceleration above 3 m·s-2 (ACC > 3) in Fullbacks (p = 0.001) than possession games. In position games, regardless of the player's role, DC and peak speed was lower in Small (p < 0.05). High-intensity accelerations/decelerations showed a heterogeneous pattern, with Central-midfielders showed larger maximal decelerations/accelerations and ACC/DEC > 3 in Large than Medium. Offensive-midfielders showed larger maximal decelerations in Large and Medium than Small and more ACC > 3 in Large than Medium. Finally, Fullbacks performed more DEC > 3 in Large than Small while Forwards did in Small than Large (p < 0.05). Due to the variability in external load responses based on player positions, practitioners should consider the type and size of position games used to adjust players` external loads during training.